A "prospective" and "retrospective" view of the hazards of a career in interventional cardiology. Issue 5 (1st November 2015) - Lange, David C.; Henry, Timothy D.
Key Points Surveyed interventional cardiologists reported frequent occupation‐related health hazards including orthopedic injury (49.4%), radiation‐related skin disease (4.8%), cataracts (5.5%), and hematologic and malignant conditions (4.8%) Further advances are needed to increase operator and staff safety to prevent future orthopedic injuries and radiation‐related diseases. Each individual interventional cardiologist needs to weigh the hazards of the profession with the benefits which are substantial as well.